W.A.B.0 (2.0) - Mohd Fuad, Mohamad Fareed Daniel; Abdullah, Muhammad Zulfahmi; A Halim, Muhammad Fahmi (Universiti Teknologi MARA, Kedah, 2019)
W.A.B.O is an application that can help people to find material in the library easily. People these day they need and application to make it easier for them to find material in the library.